The Influence of Strategic Leadership, Dynamic Capabilities and Organizational Ambidexterity on Sustainability Performance in Indonesian Regional-Owned Enterprises (BUMD) - Budiman, Budiman; Nasution, Yasmine (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Regional Owned Enterprises (ROE) in Indonesia have a strategic role in supporting regional economic development and providing important public services to the community. As a business entity owned by the local government, ROE aims not only to gain financial profit but also to improve social welfare and manage local resources efficiently. This research aims to analyze the influence of strategic leadership, dynamic capabilities, and organizational ambidexterity on the sustainability performance of Regional Owned Enterprises (ROE) in Indonesia. Strategic leadership where a leader has a clear vision and can direct the organization in optimizing the dynamic capability and ambidexterity of the organization to achieve sustainaibility performance in BUMD Indonesia. Dynamic capabilities are the capability of an organization to adapt and respond to changes in the business environment through motivation and adjustment of resources. Ambidexterity organizational has an important role in organizing to explore new opportunities (exploration) and maximize the utilization of existing resources (exploitation). This research uses a quantitative approach by distributing questionnaires to 100 ROE in Indonesia. Using the Structural Equation Model (SEM) method, the research shows that strategic leadership has a positive and significant effect on dynamic capabilities and organizational ambidexterity. Dynamic capability, organizational ambidexterity and strategic leadership have a positive and significant effect on the sustainability performance. The research results that the dynamic capability and organizational ambidexterity can also be mediating factors influencing the relationship between strategic leadership and the sustainability performance.